Identification of positive and negative regulators in the stepwise developmental progression towards infectivity in Trypanosoma brucei - Justin Y. Toh (Nature Portfolio, 2021)
Abstract Trypanosoma brucei is a protozoan parasite that causes important human and livestock diseases in sub-Saharan Africa. By overexpressing a single RNA-binding protein, RBP6, in non-infectious procyclics trypanosomes, we previously recapitulated in vitro the events occurring in the tsetse fly vector, namely the development of epimastigotes and infectious, quiescent metacyclic parasites. To identify genes involved in this developmental progression, we individually targeted 86 transcripts by RNAi in the RBP6 overexpression cell line and assessed the loss-of-function phenotypes on repositioning the kinetoplast, an organelle that contains the mitochondrial genome, the expression of BARP or brucei alanine rich protein, a marker for epimastigotes, and metacyclic variant surface glycoprotein. This screen identified 22 genes that positively or negatively regulate the stepwise progression towards infectivity at different stages. Two previously uncharacterized putative nucleic acid binding proteins emerged as potent regulators, namely the cold shock domain-containing proteins CSD1 and CSD2. RNA-Seq data from a selected group of cell lines further revealed that the components of gene expression regulatory networks identified in this study affected the abundance of a subset of transcripts in very similar fashion. Finally, our data suggest a considerable overlap between the genes that regulate the formation of stumpy bloodstream form trypanosomes and the genes that govern the development of metacyclic form parasites.